2009
DOI: 10.1002/anie.200902203
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient General Synthesis of Halide‐Free Diarylcalcium

Abstract: The Schlenk equilibrium of Ca(Ar)I can be shifted quantitatively in favor of soluble CaAr2 by the addition of stoichiometric amounts of K(OtBu). The crystallization of CaPh2 can be achieved by formation of a dinuclear 1,2‐bis(dimethylamino)ethane complex (see structure; Ca brown, N blue, C gray). The transmetalation resembles no alternative—complete metal–metal exchange does not occur in the reaction of MnPh2 with calcium powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…A similar trend was also observed for other arylcalcium species containing bridging aryl groups. 14,15 Additionally, an analogous shift was also found for related phenyllithium species containing terminal or bridging phenyl groups, respectively. 16 This calcium species most likely represents another example of an oxo-centered cluster species, occasionally observed for the aryl derivatives of the heavier alkaline-earth metals.…”
Section: ■ Introductionmentioning
confidence: 60%
“…A similar trend was also observed for other arylcalcium species containing bridging aryl groups. 14,15 Additionally, an analogous shift was also found for related phenyllithium species containing terminal or bridging phenyl groups, respectively. 16 This calcium species most likely represents another example of an oxo-centered cluster species, occasionally observed for the aryl derivatives of the heavier alkaline-earth metals.…”
Section: ■ Introductionmentioning
confidence: 60%
“…9−12 Amines were also used to stabilize arylcalcium complexes. 13 As also observed for classical Grignard reagents, a Schlenk-type equilibrium converts arylcalcium halides into homoleptic diarylcalcium and calcium dihalides depending mainly on solvent and temperature. Substitution of iodide by an alkoxide shifts this equilibrium quantitatively to the side of the homoleptic complexes.…”
Section: ■ Introductionmentioning
confidence: 90%
“…In this aim, two fundamental steps are well identified. Following the landmark description of Ca{CH(SiMe 3 ) 2 } 2 •(dioxane) 2 by Cloke and Lappert,2 Westerhausen and coworkers revealed that more than mere heavier analogues of Grignard's magnesium reagents, non‐cyclopentadienyl3 organometallic calcium‐hydrocarbyl species displayed a unique reactivity of their own 4–10. Elsewhere, reliable access to a range of stable bis(amido) Ae precursors,11 amongst which, is the highly influential Ae{N(SiMe 3 ) 2 } 2 •(THF) 2 ,12 triggered the development of synthetic tools for the rational design of heteroleptic Ca‐Ba complexes with well‐controlled coordination spheres.…”
Section: Introductionmentioning
confidence: 99%